DECREASED PAIN SCALE BASED ON CRITICAL PAIN OBSERVATION TOOL (CPOT) AND BEHAVIORAL PAIN SCALE NON-INTUBATED (BPS-NI) IN PATIENTS WITH REDUCED CONSCIOUSNESS BY CLASSICAL MUSIC INTERVENTION IN UNS HOSPITAL - Muchtar Hanafi; Faizal Muhammad; Nanang Wiyono; Betty Saptiwi (Poltekkes Kemenkes Semarang, 2019)
Patient with reduced consciousness needs attention to their comfort as well as pain during treatment. Listening to classical music caused relaxation and pain reduction. This study aimed to determine the effect of classical music on the CPOT score, BPS-NI, and cortisol levels in patients with reduced consciousness. The research was conducted by using a pretest-posttest control group design. 18 patients were divided into the control group (C) and the classical music group (M). Classical music was played for 3 days respectively that consisted of 3 sessions per day. Furthermore, each patient was tested for cortisol levels on the third day. Comparative test of mean difference between pre-intervention and post-intervention obtained significant results in CPOT (p= 0.000) and BPS-NI (p= 0.001) measurements in all groups. Tukey's post-hoc test obtained significant results in which the M group had a lower mean score. The mean of cortisol level was higher in M group (14.7 μg/dL) compared to the C group (12.96 μg/dL), although not significant statistically (p= 0.67). Listening to classical music for patients with reduced consciousness decreased the pain scale. This was supported by the average of cortisol levels that were higher in the M group, considering that cortisol was a hormone that prevents pain.